PKM Kelompok Budidaya Rumput Laut Kecamatan Bangkala Kabupaten Jeneponto - Najamuddin, Najamuddin -; Rustam, Rustam; Baso, Aris (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Seaweed cultivation activities have long developed, but productivity tends to decrease over time due to various environmental factors. Efforts to increase productivity are minimal, both from government agencies and from the community itself. The results of previous studies indicate that the integration of seaweed cultivation can increase the income of seaweed farmers. The main problems of partners include: low productivity due to fish pest disturbance and technical cultivation, poor business management, low income and variations in seaweed growth. The main targets include: (1) increasing income of partner groups through fishing activities; (2) increasing production of partner groups through fostering seaweed cultivation techniques; (3) increasing business productivity through fostering production and business management. The method of approach is to solve problems with group members (partners), namely: counseling, training, piloting, guidance and assistance as well as practical learning (learning by doing). Counseling includes: technical seaweed cultivation, fishing techniques, group management, business management. Practical training: improvement of construction framework for seaweed cultivation, construction of fishing gear, application of fishing technology. Furthermore, assistance and monitoring and evaluation of the success of the implementation of community partnership program (PKM). The results of extension show that the group realizes that the potential of fish around seaweed cultivation has not been utilized properly. The fish around seaweed cultivation can be utilized by using fish trap or gill net. The results of field observations showed that the bubu could not be operated in strong current conditions and caused partial flooding. In addition, the availability of bait is a limiting factor in the operation of bubu. The bait commonly used in catching rabbit fish is silk moss which is present around the rainy season. Fish caught include: rabbit fish, grouper, mangrove red snapper, barramundi. Weather conditions that are less friendly make the fish catches not as expected.